The prevalence of osteoporosis in China, a community based cohort study of osteoporosis - Wang, Jing; Shu, Bing; Tang, De-zhi; Li, Chen-guang; Xie, Xing-wen; Jiang, Li-juan; Jiang, Xiao-bing; Chen, Bo-lai; Lin, Xin-chao; Wei, Xu; Leng, Xiang-yang; Liao, Zhang-yu; et al. (Frontiers in Public Health, 2023)
Background: Osteoporosis has already been a growing health concern worldwide. The influence of living area, lifestyle, socioeconomic and medical conditions on the occurrence of osteoporosis in the middle-aged and elderly people in China has not been fully addressed. Methods: The study was a multicenter cross-sectional study on the middle-aged and elderly permanent residents, which gathered information of 22081 residents from June 2015 to August 2021 in 7 representative regions of China. The bone mineral density of lumbar vertebrae and hip were determined using the dual-energy X-ray absorptiometry densitometer instruments. Serum levels of bone metabolism markers were also measured. Information about education, smoking and chronic diseases were also collected through face-to-face interviews. Age-standardized prevalence and 95% confidence intervals (CIs) of osteopenia and osteoporosis by various criteria were estimated by subgroups and overall based on the data of China 2010 census. The relationships between the osteoporosis or osteopenia and sociodemographic variables or other factors were examined using univariate linear models and multivariable multinomial logit analyses. Results: After screening, 19848 participants (90%) were enrolled for the final analysis. The age-standardized prevalence of osteoporosis was estimated to be 33.49% (95% CI, 32.80%-34.18%) in the middle-aged and elderly Chinese permanent residents, for men and women was 20.73% (95% CI, 19.58%-21.87%) and 38.05% (95% CI, 37.22%-38.89%) respectively. The serum concentrations of bone metabolic markers, and calcium and phosphorus metabolism were influenced by age, body mass index (BMI), gender, education level, regions and bone mass status. Women, aged 60 or above, BMI lower than 18.5 kg/m2, low education level including middle school, primary school and no formal education as well as current regular smoking, a history of fracture were all significantly associated with a higher risk of osteoporosis and osteopenia in the middle-aged and elderly people. Conclusions: This study revealed dramatic regional differences in osteoporosis prevalence in China, and female, aged 60 or older, low BMI, low education level, current regular smoking, and a history of fracture were associated with a high risk of osteoporosis. More prevention and treatment resources should be invested into particular population exposed to these risk factors.